Anaesthetic method and short-term outcomes of preterm infants delivered by caesarean section in a tertiary hospital in South Africa - Stander, Raphaella (Department of Paediatrics and Child Health, 2022)
Background. There are inconsistent published data describing the influence of anaesthetic type during caesarean section (CS), on outcomes of preterm neonates. Objectives. To describe indications and type of anaesthesia in preterm neonates and to describe short-term outcomes, comparing spinal anaesthesia (SA) to general anaesthesia (GA). Methods. Data were collected retrospectively on preterm babies born at 28 – 35 weeks' gestation by CS, between 1 January and 30 Sep 2014 at Groote Schuur Hospital, Cape Town, South Africa. Babies with missing data were excluded. The largest group of babies with similar indications for delivery were identified from the theatre register. Baseline characteristics and short-term outcomes for this group were extracted from an existing prospective data base, and compared between those delivered under SA and GA. Results. Data were available for 226 deliveries, having excluded 23 with incomplete data. Most babies (75%) were delivered under SA. The most common indication for CS was ‘cardiotocograph abnormalities,' in 139 deliveries. Within this group, SA was more frequent (81.7% vs. 12.9%) while GA was associated with lower Apgar scores (p < 0.001) and more intubation at birth (p = 0.004). There was no difference in mortality when comparing SA with GA. Conclusion. Our data suggest a sedative effect of maternal GA on preterm babies delivered by CS, and the need for staff with advanced resuscitation skills. This study provides novel baseline data in our setting, but these data need to be validated in a prospective study.